Pandemic Vibrio cholerae shuts down site-specific recombination to retain an interbacterial defence mechanism - Francis J. Santoriello; Lina Michel; Daniel Unterweger; Stefan Pukatzki (Nature Communications, 2020)
Vibrio cholerae uses a type VI secretion system (T6SS) to kill neighbouring competitors. Here, Santoriello et al. show that a T6SS gene cluster (Aux3) exists as a mobile, prophage-like element in some environmental strains, and as a stable truncated form in pandemic isolates. They propose that Aux3 acquisition increased competitive fitness of pre-pandemic V. cholerae.